Compliance with hand hygiene in clinical nurses and improvement strategy (临床护理人员手卫生依从性现状及对策) - LU Jiaojiao (卢姣姣); HONG Hanhan (洪涵涵) (中西医结合护理)
This paper briefly introduce the relationship between hand hygiene and nosocomial infection, and summarize the status quo of compliance with hand hygiene in clinical nurses. The influencing factors of hand hygiene and improvement strategy were also discussed in this paper, in order to improve the present situation of hand hygiene in clinical nurses, reduce the risk of nosocomial infection and promoting the patient-nurse safety (本文通过阐述手卫生与医院感染的关系, 总结手卫生在国内临床护理人员中的执行现状, 归纳了影响手卫生依从性的因素及应对策略, 以期改善护理人员的手卫生现状、减少医院感染的发生、有效保障护患双方的安全。)